Wilson, Patriotic Correctness - Academic Freedom And Its Enemies - Broadwater, Jeff (Teaching History: A Journal of Methods, 2009)
The Chicago writer and liberal activist John K. Wilson observes near the end of Patriotic Correctness that violations of academic freedom in higher education are exceptions to the rule . That conclusion might surprise his readers; Patriotic Correctness otherwise tells a depressing story of the relentless efforts of interest groups, legislators, and college administrators to silence dissent and debate. Conservatives can be targeted, especially by bureaucrats who fear controversy and criticism even more than radical politics. Yet, Wilson writes, it is "a dirty little secret of higher education ... that left-wing political activists encounter the most discrimination of anyone." The results are apolitical teachers, complacent campuses, and apathetic students.